The constitution of European democracy - Grimm, Dieter, 1937- (Oxford : Oxford University Press, 2017)
This text highlights Europe's democracy problem. The common argument throughout is that the European Union has become over-constitutionalized, and Grimm makes recommendations for solving this. Grimm also outlines the EU's legitimacy deficit and the proposed remedy of 'parliamentarization'.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 19, 2017).
Keywords: Constitutional law -- Europe; Democracy -- Europe; European Union; Constitutional law -- European Union countries; Democracy -- European Union countries; Law; Laws of specific jurisdictions & specific areas of law